(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research paper Observes and analyzes the Implementation of Republic Act 7438, the right of the arrested suspect, detained or under custodial investigation, with the help of our local authorities and community participants to ensure that the arrested suspect exercises their rights in Bagong Silangan Quezon City. To answer the problem, the researcher gathered data with the help of questionnaires that detailed the rights of a suspect that should be exercised before and after arrest, detaining, and custodial investigation. The result also revealed that the Implementation of R.A 7438 has already been given and exercised to the suspect who had been arrested. The implication of this study could be used to determine how R.A. 7438 helps the arrested suspect, detained or under custodial investigation, enjoy their rights. The Data gathered by the researcher in the Implementation of Republic Act 7438 showed that the rights of the arrested suspect had already been exercised by the Quezon City Police District Station 13 (Bagong Silangan) Police Substation. Most of the respondents, including the citizen of Bagong Silangan Quezon City, agree that the QCPD Station 13 exercised the Implementation of R.A 7438.